The walking dead. Vol. 17, Something to fear - Kirkman, Robert (Kirkman, Robert. Walking dead., 2012)
In this volume of the NYT bestselling survival horror, Rick and his band of survivors work to build a larger network of thriving communities, and soon discover that Negan's "Saviors" prove to be a larger threat than they could have fathomed. Crossing Negan will lead to serious, dire consequences for the group; it seems that for the first time since the Governor's reign of terror that Rick may have Something to Fear.